PBG 5. Multi-location adaptability test of direct seeded Rainfed Rice (Oryza sativa L.) lines and evaluation of test locations (The Philippine Journal of Crop Science, 2018)
Climate change coupled with poor irrigation system has rapidly increased the drought-prone areas for direct-seeded rainfed-lowland ecosystem in the Philippines. In response, breeding institutions have continuously developed rainfed lowland varieties for farmers’ utilization in these areas. The target population of environments (TPE) for rainfed ecosystem is unique and unpredictable resulting in adoption of few, out of many, released varieties by the farmers. This experiment was conducted to i) evaluate the adaptability of advanced rainfed rice lines in four locations, ii)evaluate the testing environments for rainfed lowland rice lines, and iii) expound the effect of differences in hydrologic regime and management practices among locations on the genotype and environment means. Genotype was treated as fixed effect to compare the new genotypes with existing varieties. The genotype main effects showed that rainfed rice lines G60 (GSR IR2-DQ3-D1-S1), G30 (IR 107891-B-B-1253-1-1), G43 (IR 106516-1-2-2-2), G7 (Raeline 10) and G34 (GSR IR2-DQ17-S1-S1) are highly yielding and stable across locations; while genotype x environment effects indicate that some entries are specifically adaptable like G4 (Raeline 6) in Camarines sur, G21 (PR43482-13-1-1-3) in Cagayan and G58 (GSR Ir2-DQ25-S2-Y1) in iloilo. Based on one-stage multi-location analysis, only G60 (GSR IR2-DQ3-D1-S1) had significant yield difference (a=5% Dunetts Test) with a check variety. PSB Rc 68. The GE biplot analysis revealed that the most discriminating environment is Camarines Sur; the most representative is Cagayan; while the highest mean was from iloilo. The conjunction of ground and/or paddy water level, especially during panicle initiation and grain-filling period and the amount of farm inputs applied, were the major factors affecting the genotype and environment means.